Differences in Caries Status and Risk Factors among Privileged and Unprivileged Children in Colombia. (2018)
OBJECTIVE: The objective of this study was to compare the ICDAS-II caries status and caries-related factors among children from rural and urban schools in Pasto, Colombia. MATERIALS AND METHODS: The study included 120 children (4 - 6 year- old children) from rural (privileged) and urban (unprivileged) schools. Caries was evaluated using the ICDAS-II criteria. A survey about the factors related to the presence of caries was applied. Chi-square and Fisher's tests were used to assess the differences in each study variable between the two groups. A Mann-Whitney U test was used to compare the number of teeth, per ICDAS-II category, between the groups. Negative binomial regression was used to estimate the percentage change in the mean number of teeth, per ICDAS-II category, among the rural and urban students. RESULTS: Significant differences were found between the rural and urban students for the ICDAS-II 0 and 3-6 categories (p<0.001). The mean number of teeth with moderate-to-severe caries status increased 233% in children from the rural school compared to those attending the urban school (p=0.0). Toothbrushing frequency (p=0.006), cariogenic diet, time elapsed from last dental visit, socioeconomic status, and type of health regime (p<0.001) were among the significant factors related to the rural and urban schools. CONCLUSIONS: This was the first study to compare ICDAS-II caries status between rural and urban students in Colombia. A worse caries status was found in rural students. This study identified the socioeconomic and clinical factors to guide specific interventions for rural children by modifying the available oral health promotion and disease prevention programs.